Flavonoides y alcaloides de Lupinus ballianus C.P. Smith con actividad antibacteriana y antifúngica - Fuertes Ruitón, César M. (1998)
The leaves of Lupinus C.P. Smith were colected from the highlands in Lima, it contains among other 5 flavonoids and 5 alkaloids.The flavonoid genistein was characterized by means of visible-UV spectroscopy, observing the bathochromic and hipsochomic movements of the spectra with sodium methoxide, aluminuin chloride, boric acid and sodium acetate reagents.The IR spectrum reveals the presence of the alkaloid lupenin or hydroxylupenin.Both the flavonoid and the alkaloid show a strong antibacterial activity and the alkaloid shows in addition of this property an antifungic activity.